2019
DOI: 10.1186/s13018-019-1487-0
|View full text |Cite
|
Sign up to set email alerts
|

Early and short-segment anterior spinal fusion for cervical spinal cord injury without fracture and dislocation can achieve more significant neurological recovery: a retrospective study based on the current medical system in southern China

Abstract: ObjectiveThe purpose of this study was to investigate the effects of the number of fused segments, the timing of surgery and their interaction on the prognosis of patients with cervical spinal cord injury without fracture and dislocation (CSCIWFD), and to determine the appropriate time restrictions for early surgery in CSCIWFD patients based on the current diagnosis and treatment system in southern China.MethodsCSCIWFD patients who underwent anterior cervical decompression and internal fusion (ACDF) from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Posterior spinal fusion is the procedure of choice for patients with trauma, spinal infection, spinal deformities, and degenerative spinal diseases [ 16 ]. The total number of operations in PSL has been rising annually, especially in China [ 17 , 18 ]. Significant blood loss is the most frequent surgical complication and receiving a great deal of attention in the spinal surgeon, as well as anesthesiologist [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posterior spinal fusion is the procedure of choice for patients with trauma, spinal infection, spinal deformities, and degenerative spinal diseases [ 16 ]. The total number of operations in PSL has been rising annually, especially in China [ 17 , 18 ]. Significant blood loss is the most frequent surgical complication and receiving a great deal of attention in the spinal surgeon, as well as anesthesiologist [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 12 studies were included. [9][10][11][12][13][14][15][16][17][18][19][20] The literature screening process is shown in Figure 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The risk of bias in blinding of outcome assessment (detection bias), incomplete outcome data (attrition bias), selective reporting (reporting bias), and other sources of bias was low for all studies. Nine studies [9,10,12,14,[16][17][18][19][20] showed a high risk of bias for random sequence generation and allocation concealment (selection bias).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Posterior spinal fusion is the procedure of choice for patients with trauma, spinal infection, spinal deformities and degenerative spinal diseases (16). The total number of operations in PSL has been rising annually, especially in China (17,18). Signi cant blood loss is the most frequent surgical complication and receiving a great deal of attention in the spinal surgeon, as well as anesthesiologist (19).…”
Section: Discussionmentioning
confidence: 99%